Post-traumatic growth in cancer survivors: what is its extent and what are important determinants? - Blickle, Patricia; Schmidt, Martina; Steindorf, Karen (International journal of clinical and health psychology, 2024)
Background/Objective - The aim was to investigate the extent and longitudinal determinants of post-traumatic growth (PTG) in cancer survivors. - Methods - A sample of 1316 cancer survivors with various cancer types was examined using the EORTC QLQ-FA12 to assess fatigue, the EORTC QLQ-C30 pain items to assess pain and the Patient Health Questionnaire (PHQ-4) to assess emotional distress two years after diagnosis (t0). Additionally, patients rated how well they felt informed about fatigue at t0. PTG was assessed with the 21-item PTG-Inventory four years after diagnosis (t1) comprising the five subdimensions appreciation of life, relation to others, personal strengths, new possibilities and spiritual change. - Results - Regarding the extent of PTG, most positive developments were experienced in the PTG subdimension appreciation of life whereas the subdimension spiritual change was the least pronounced domain. Fatigue, pain and emotional distress were longitudinal but non-linear predictors of long-term PTG. Additionally, poor informedness about fatigue was associated with less PTG. - Conclusions - PTG can be perceived even years after a traumatic cancer event and is longitudinally associated with common cancer side effects like fatigue, emotional distress and pain. Further research into the role of individuals' informedness contributing to PTG is needed.
Online verfügbar 14 October 2023, Version des Artikels 14 October 2023
Gesehen am 06.05.2024